Just multiple them together and u get 693
Answer:
1/12
Step-by-step explanation:
1/2 ÷ 6
is the same as;
1/2 × 1/6 = 1/12
1 is 1
2 is going to be -8x to the second minus 6 x
3 is 3 plus three x two minus seven x plus two xx 2 minus 6xto the 2
4 is 11
Let the original number be ‘x’
Then half of that number= 1/2x or simply x/2
Similarly one fifth of that number = x/5
According to the question
x+x/2+x/5=51
Taking LCM
10x/10+2x/10+5x/10=51
Multiplying 10 throughout
10x+2x+5x=510
17x=510
x=510/17
Therefore x=30
Answer:
Step-by-step explanation:
7) 2ab + 4ac = 2*a*b + 2 *2 *a*c
= 2a(b + 2c)
![\dfrac{2ab^{2}c}{2ab+4ac}=\dfrac{2*a* b^{2}*c}{2a(b+2c)}\\\\\\\text{2a in the denominator and numerator get cancelled}\\\\ = \dfrac{b^{2}c}{b+2c}](https://tex.z-dn.net/?f=%5Cdfrac%7B2ab%5E%7B2%7Dc%7D%7B2ab%2B4ac%7D%3D%5Cdfrac%7B2%2Aa%2A%20b%5E%7B2%7D%2Ac%7D%7B2a%28b%2B2c%29%7D%5C%5C%5C%5C%5C%5C%5Ctext%7B2a%20in%20the%20denominator%20and%20numerator%20get%20cancelled%7D%5C%5C%5C%5C%20%3D%20%5Cdfrac%7Bb%5E%7B2%7Dc%7D%7Bb%2B2c%7D)
8) ac - a²c² = c( a - a²c)
bc - abc = c(b - ab)
![\dfrac{ac - a^{2}c^{2}}{bc-abc^{2}}=\dfrac{c(a-a^{2}c)}{c(b-ab)}\\\\](https://tex.z-dn.net/?f=%5Cdfrac%7Bac%20-%20a%5E%7B2%7Dc%5E%7B2%7D%7D%7Bbc-abc%5E%7B2%7D%7D%3D%5Cdfrac%7Bc%28a-a%5E%7B2%7Dc%29%7D%7Bc%28b-ab%29%7D%5C%5C%5C%5C)
![=\dfrac{a-a^{2}c}{b-abc}](https://tex.z-dn.net/?f=%3D%5Cdfrac%7Ba-a%5E%7B2%7Dc%7D%7Bb-abc%7D)
9) b²+ 4b - 5 = b² + 5b - 1b - 5
= b(b + 5) - 1(b + 5)
= (b +5)(b - 1)
b² + 8b + 15 = b² + 5b + 3b + 15
= b(b + 5) + 3(b + 5)
= (b + 5 )(b + 3)
![\dfrac{b^{2}+4b-5}{b^{2}+8b+15}=\dfrac{(b+5)(b-1)}{(b+5)(b+3)}\\\\\\](https://tex.z-dn.net/?f=%5Cdfrac%7Bb%5E%7B2%7D%2B4b-5%7D%7Bb%5E%7B2%7D%2B8b%2B15%7D%3D%5Cdfrac%7B%28b%2B5%29%28b-1%29%7D%7B%28b%2B5%29%28b%2B3%29%7D%5C%5C%5C%5C%5C%5C)
![=\dfrac{b-1}{b+3}](https://tex.z-dn.net/?f=%3D%5Cdfrac%7Bb-1%7D%7Bb%2B3%7D)